Application of The TaRL Approach to Improve Science Learning Outcomes Students on Ecosystem Materials - Hidayati Hidayati; Sugianoor Sugianoor (Universitas Lambung Mangkurat, 2024)
This classroom action research aims to improve student learning outcomes by applying the Teaching at the Right Level (TaRL) concept to the ecosystem concept. TaRL is an approach to learning that aims to ensure that students understand the subject matter being taught. It focuses on identifying students' levels of understanding and aligning them with the appropriate level of learning. The research method uses descriptive language with two cycles. Data analysis techniques use qualitative and quantitative analysis. Each cycle consists of planning, implementation, observation, and reflection. The subjects of this research were 40 class XD students at SMAN 7 Banjarmasin for the 2022–2023 academic year. The learning process in TaRL groups students into three categories, namely students with intermediate, above, and below-average levels. Material and problems are given according to their level of learning, but still with the same learning objectives and outcomes. Student learning outcomes in learning activities increased from pre-cycle, showing a classical completeness of 32.5%; cycle I showed a classical completeness of 62.5%; and cycle II had reached the success indicator with a classical completeness of 87.5%. Research using the TaRL approach has improved the science learning outcomes of class XD students at SMA Negeri 7 Banjarmasin.